Yet another introduction to dark matter - Plehn, Tilman (Arxiv, 2017)
Dark matter is a widely discussed topic in contemporary particle physics. Written strictly in the language of particle physics and quantum field theory, these notes focus on a set of standard calculations needed to understand weakly interacting dark matter candidates. After introducing some general features of these dark matter agents and their main competitors, we introduce the Higgs portal scalar and supersymmetric neutralinos as our default models. They guide us through four experimental aspects: the dark matter relic density extracted from the cosmic microwave background, indirect detection including the Fermi galactic center excess, direct detection, and collider searches. Alternative approaches like an effective theory of dark matter and simplified models naturally follow from the discussions of these four experimental directions.